2021
DOI: 10.21037/tau-21-309
|View full text |Cite
|
Sign up to set email alerts
|

Modified Takazawa anatomical classification of renal pelvicalyceal system based on three-dimensional virtual reconstruction models

Abstract: Background: Previous classification of renal pelvicalyceal anatomical structure may be difficult to intuitively understand and unpractical for endourological surgery. We aim to put forward a modified Takazawa anatomical classification of renal pelvicalyceal system based on three-dimensional (3D) virtual reconstruction models for endourological surgery.Methods: We retrospectively collected data on 225 patients (320 kidneys) in total between Apr. 2017 and Dec. 2020, spatial anatomical structure of renal pelvis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A recent study proposed a variation of the classification of the renal collecting system including 5 types of renal pelvis: Type A - a single pelvis without bifurcated branch and subclassified into three subtypes according to the cross- sectional area of renal pelvis: Type A1 - If the cross-sectional area ratio of the pelvis to the UPJ is lower than 4 times, the pelvis is considered to be type A1, which is a slimline pelvis morphology, Type A2 - formed by a typical funnel shaped pelvis and the cross-sectional area of the pelvis is about 4–16 times larger than that of the UPJ, and this subtype is the most frequently observed standard morphology; and Type A3 - subtype that included a broad pelvis morphology forming a large box shaped pelvis with the cross-sectional area ratio of the pelvis to the UPJ greater than 16 times. A divided pelvis with bifurcated branches is seen as Type B and subclassified into two subtypes: Type B1 with the wide and flat lower calyx infundibulum, and Type B2 with the narrow and steep lower calyx infundibulum ( 30 ). However, in our opinion, this division proposed by these authors includes some alterations that already are considered by Sampaio ( 18 , 19 ).…”
Section: Calyces Position In Relation To Edge Of the Kidneymentioning
confidence: 99%
“…A recent study proposed a variation of the classification of the renal collecting system including 5 types of renal pelvis: Type A - a single pelvis without bifurcated branch and subclassified into three subtypes according to the cross- sectional area of renal pelvis: Type A1 - If the cross-sectional area ratio of the pelvis to the UPJ is lower than 4 times, the pelvis is considered to be type A1, which is a slimline pelvis morphology, Type A2 - formed by a typical funnel shaped pelvis and the cross-sectional area of the pelvis is about 4–16 times larger than that of the UPJ, and this subtype is the most frequently observed standard morphology; and Type A3 - subtype that included a broad pelvis morphology forming a large box shaped pelvis with the cross-sectional area ratio of the pelvis to the UPJ greater than 16 times. A divided pelvis with bifurcated branches is seen as Type B and subclassified into two subtypes: Type B1 with the wide and flat lower calyx infundibulum, and Type B2 with the narrow and steep lower calyx infundibulum ( 30 ). However, in our opinion, this division proposed by these authors includes some alterations that already are considered by Sampaio ( 18 , 19 ).…”
Section: Calyces Position In Relation To Edge Of the Kidneymentioning
confidence: 99%
“…The interquartile range of the cross-sectional area of the renal pelvis in a single pelvis (Type A) spans a wide range, from 41 to 111 mm. Furthermore, in the case of a Type B pelvis, the crosssectional area of lower bifurcated branches in a divided pelvis constitutes a significantly smaller space (on average, 26 mm) [6]. The volume of fluid in which laser activation takes place is a crucial factor in determining the degree of temperature elevation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported varying numbers of pyramids ranging between 5 and 20 pyramids. 9 However, studies have also reported the presence of subtle renal columns within pyramids; these subdivisions are sometimes described as fused secondary pyramids or subpyramids that share the same papillary tip. [10][11][12] Thus, the number of pyramids in a human kidney may be less than the original number of renal lobes because of these fusions.…”
Section: Introductionmentioning
confidence: 99%